Learning About Outgroups: The Impact of Broad Versus Deep Interactions - Anujit Chakraborty; Arkadev Ghosh; Matt Lowe; Gareth Nellis (CESifo GmbH, 2024)
We hypothesize that broad contact, involving brief interactions with multiple outgroup members, and deep contact, meaning longer interactions with a single outgroup member, play distinct roles in shaping intergroup relations. We set up a factory in India and recruited Hindu and Muslim men to work in pairs on joint production tasks. We randomly assigned participants to work either with the same ingroup or outgroup partner daily (deep contact), a different outgroup partner each day (broad contact), or to a control group. While deep contact strengthens social and economic ties with the outgroup partner interacted with, only broad contact reduces misperceptions about outgroup strangers. These findings align with a model in which independent sampling (observing multiple outgroup members) promotes learning about outgroups more than prolonged interaction with a single individual does. Nevertheless, neither type of contact changes behavior toward the wider outgroup.
Keywords: J15; C93; D91; Z12; 330; intergroup contact; social learning; religion; productivity